Effect of ionic liquid in a pressurized reactor to enhance CO2 photocatalytic reduction at TiO2 modified by gold nanoparticles - Perini, João Angelo Lima [UNESP]; Irikura, Kallyni [UNESP]; Torquato, Lilian D. Moura [UNESP]; Flor, Jader Barbosa da S. [UNESP]; Zanoni, Maria V. Boldrin [UNESP] (Elsevier, 2022)
This work describes the synergic effect of gold nanoparticles as co-catalyst on TiO2 nanotubes (TNT/AuNP) in aqueous medium containing the ionic liquid (IL) 1-Butyl-3-methylimidazolium tetrafluoroborate, in a pressurized photocatalytic reactor, as a good strategy to enhance CO2 conversion into value-added products. The surface plasmon resonance of the gold NPs improve the photoexcitation under visible light and slightly change the TNT band gap from 3.2 to 2.9 eV. Methanol production using TNT/AuNP in aqueous medium containing 2% (v/v) BMIM-BF4, 1 g L−1 Na2SO3 as a hole scavenger, under 5 atm pressure and solar irradiation, produce up to 279.6 µM (µmol L−1) of methanol and 98.8 µM of methane, with the quantum yield of 1.12% at 440 nm. Isotope-labeled studies by GC/MS proved that 13CO2 is the source for photoproduction of 13CH3OH. The results indicate that the combination of the Au co-catalyst size, high pressure, and IL can provide efficient modulation of CO2 conversion.
Keywords: BMIM-BF4; Quantum yield; Solar simulator; Solubility; Surface plasmon resonance